DE-COLONIZING POLITICAL BOUNDARIES IN CENTRAL ASIA - N. T. Nurulla-Khodzhaeva (Vestnik MGIMO-Universiteta, 2018)
The discourse of “borders” and decolonisation in the context of Central Asia has been a path unexplored until this moment, therefore a “startup” approach is logical. This “border” is a phenomenon that continuously shapes and transforms itself, therefore giving new light to the understanding of history and culture of Central Asia.  This guiding principle influences the relationships that are built between close and distant neighbors on the planet. The other side opposite of this the notion is that of a modern state, that does not tolerate the lack of an identity; it requires one to cement a belonging to a certain geographical unit. The history of “modern and national” is articulated through the juxtaposition of “I” and “Other” (“outside of the border”). The interconnections of borders, states in Central Asia, and their orientalist platform do not lend themselves to an easy solution. The border does not hide or deny its artificiality, it has become ingrained as the norm. The innocent process of modern statebuilding is ensued by its «Westphalian» foundation. Naturally such interpretation of modern state raises more questions than answers. These questions are related to the uncertainty of the past of Central Asia, as well as the it’s bordering lands. The most fascinating characteristic of such uncertainty, is that it displays multi-locality (or otherwise, multi-community) rather than “multi-nationality. Inside Dushanbe, Samarkand, Tashkent, and Bukhara most of these communities are distinguished by their national diversity, which is a given. This “rhythm” continues to make the region more open not just to each other internally, but also globally. Therefore, in this context the remaining colonial heritage should be treated differently, without constant references to “borders”, without attempts to reproduce the sense of subordination of former colonization. In this regard, the proximity (geographical, cultural, “Soviet”) to Russia should help with understanding its own Eurasian of interconnectedness. A real equilateral dialogue, with the incorporation of the accumulated common academic heritage. i.e. sovereignty (in which all the inhabitants of the republics are believed) cannot be represented as a voluntary application of the universally declared right to self-determination. All five members of the Central Asian “club” march and convince each other, that the abstract universal form of international relations in no way makes our common «stan» Eurocentric. While Central Asian involvement in so-called “national” cultures is difficult to materialize with its variety of languages, traditions, styles. Hence the difficulty of a sense of «multinationality». This should rather be treated and seen “multi-locality” (or otherwise “multi-community”) in Dushanbe, Samarkand, Tashkent, Bukhara. National diversity of these communities are naturally inherent. This “rhythm” continues to make the region more open to each other and to the world, transforming it into a “field” located on beyond good, evil, right or wrong. The region is where the diversity meets.